Pengaruh Harga, Kualitas Produk dan Promosi Terhadap Minat Beli Ulang Konsumen Coffeeshop Budaya Kopi Kota Tegal - Sari Wiyanti; Mahardina Yunidar Rahma; Poppy Kusuma Buana Rahajeng Putri; Amelia Dwi Pramushinta (EBISMAN eBisnis Manajemen, 2025)
This study examines the impact of price, product quality, and promotion on consumer repurchase intention in coffee culture, specifically focusing on Budaya Kopi in Tegal City. As the coffee shop industry experiences rapid growth, understanding the factors that influence consumer behavior becomes crucial. This research aims to identify whether perceptions of price positively affect repurchase intentions, assess the significant influence of product quality, and evaluate the role of promotional strategies on consumer buying decisions. Utilizing a quantitative approach, data will be collected through surveys targeting customers of Budaya Kopi. The findings are expected to provide valuable insights for coffee shop owners in developing effective marketing strategies that cater to consumer preferences, ultimately enhancing customer loyalty and business performance.